2018
DOI: 10.1016/j.scitotenv.2017.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Parental exposure to bisphenol A and its analogs influences zebrafish offspring immunity

Abstract: Transgenerational effects of environmental pollutants on humans and animals are complex. Thus, we used zebrafish to evaluate the effects of parental whole-life cycle exposure to bisphenol A and its analogs (bisphenol S and F) on offspring innate immunity. At adulthood, offspring were examined with/without continued chemicals treatment until 72h post-fertilization (hpf). To measure offspring immune function, larvae at 72 hpf were expose for 24h with/without the viral mimic polyinosinic-cytidylic acid (Poly I:C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…include endocrine-disrupting compounds such as phytoestrogens (Patisaul and Jefferson 2010), polychlorinated biphenyls (Li et al 2016), polycyclic aromatic hydrocarbons (PAH) (Zhang et al 2016), pesticides (Kida et al 2018), dioxins (Brulport et al 2017), phthalates and plastic ingredients (Dong et al 2018), and natural and synthetic hormones (Ben Fredj et al 2017). These substances are found in wastewater treatment plants and in the natural environment in rivers, lakes, and even oceans (do Nascimento et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…include endocrine-disrupting compounds such as phytoestrogens (Patisaul and Jefferson 2010), polychlorinated biphenyls (Li et al 2016), polycyclic aromatic hydrocarbons (PAH) (Zhang et al 2016), pesticides (Kida et al 2018), dioxins (Brulport et al 2017), phthalates and plastic ingredients (Dong et al 2018), and natural and synthetic hormones (Ben Fredj et al 2017). These substances are found in wastewater treatment plants and in the natural environment in rivers, lakes, and even oceans (do Nascimento et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…levels of immunoglobulin M (IgM), C-reaction Protein (CRP), and complement component 3] [ 87 91 ]. Although BPS assays on the fish immune system have not been extensively undertaken to date, a recent study suggested that immune defense is diminished by exposing parental generations to environmentally relevant concentrations of BPS in zebrafish [ 92 ]. Suppressive effects of BaP on immune systems have been extensively reviewed in teleost [ 93 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, BPS functions as a weak androgen receptor (AR) agonist (Molina-Molina et al 2013 ; Zenata et al 2017 ). A number of authors have demonstrated in laboratory studies that BPS beyond endocrine disruptive activity is cytotoxic, immunotoxic, neurotoxic, and genotoxic (Peyre et al 2014 ; Rochester and Bolden 2015 ; Feng et al 2016 ; Zhang et al 2016 ; Dong et al 2018 ; Qiu et al 2018 ; Mas et al 2020 ). Due to the disruption of centrosome function and microtubule organization, BPS such as BPA exerts a vast spectrum of cancer-promoting effects, but it incites a stronger reproductive and DNA damage response than BPA (Ho et al 2017 ; Deng et al 2018 ; Lin et al 2019 ; Song et al 2019 ).…”
Section: Endocrine-disrupting Chemicalsmentioning
confidence: 99%